Digitalization of accounting and auditing as a factor in increasing the efficiency of national resource management (Journal of Economic Research & Business Administration, 2024)
National resources are an important element of economic development, determining the possibilities and prospects of the country, and their effective management contributes to the achievement of economic growth and prosperity of any country. Improving the quality of national resource management will significantly increase the output of the gross product. The accounting and auditing industry is critical in organizing management and making informed decisions in ensuring compliance with regulatory requirements for the efficient use of national resources. Recently, these industries have seen a shift towards digital transformation. Recently, these industries have seen a shift towards digital transformation, which in the modern world affects many aspects from business processes and technologies to employee competency assessment. And as a result, digital innovations have affected the accounting and auditing system. New accounting and auditing tools have emerged, making the system even more efficient and informative, which in turn contributes to the growth of prosperity in any country. At the same time, there is currently no model for the development of accounting and auditing that is being transformed in the direction of digitalization of the management of the country's national resources. The article reveals the features of the transformation of accounting and auditing associated with digitalization, and how this process contributes to the efficiency of national resource management. The object of the study was digital accounting and auditing technologies and their application in the management of national resources. The directions of modernization of accounting and auditing processes related to the use of digital data in the processing of reporting information, how to obtain financial information for its users today, using advanced digital technologies, and what impact technological innovations have on accounting and auditing of national resources are studied. The dialectical and empirical methods are used as the main methodological principles of the study. The main result of the study is a generalization of the stages of transformation of accounting and auditing processes in modern conditions of digitalization, aimed at improving the efficiency of managing the country's national resources. The results obtained can be used by economic entities to strengthen their competitive advantages in the context of global digital transformation.Key words: accounting, audit, digitalization, electronic reporting, national resources, blockchain technology, robotization.